ANALISIS KEMAMPUAN PEMAHAMAN MATEMATIKA SISWA DITINJAU DARI KESULITAN BELAJAR PADA MASA PANDEMIC COVID-19 - Lismawati Sitorus; Eva Yanti Siregar; Roslian Lubis (JURNAL MathEdu (Mathematic Education Journal), 2022)
Abstract This study aims to know the description of students’ ability to understand mathematics and what the factors that affect students’ ability to understand mathematics in terms of learning difficulties during the Covid-19 Pandemic. This research was conducted at the Sosorgonting Adventist Private Elementary School. The type of research used qualitative method. Data collection techniques used observation, questionnaires, interviews, tests and documentation. Data analysis techniques used data reduction, data presentation and conclusion drawing. The results showed that the students' ability to understand mathematics was still low, 10 students did not complete and 3 students completed the specified KKM score. The results of the distributed questionnaires obtained showed the average is 72.31 which mean that students have learning difficulties in the high category. Students' ability to understand mathematics is influenced by several factors, namely external and internal factors. Some external factors include time constraints, family pressure, lack of support in the surrounding environment and financial problems. In addition, there are internal factors related to discipline, interests, and physical health.